SEDENTARY LIFESTYLE AS A RISK OF OBESITY IN ADOLESCENTS IN TUBAN DISTRICT - Binti Yunariyah; Wahyuningsih Triana Nugraheni; Titik Sumiatin (Nursing Sciences Journal, 2024)
Healthy Living Community Movement (GERMAS), one of which is through physical activity carried out for at least 30 minutes per day, but in fact, many people, especially teenagers, are lazy to do it. Sedentary lifestyle is now a serious problem and an important issue in public health because it is carried out for a long period of time so that it has a negative impact on health (Rahma & Wirjatmadi, 2020). The purpose of this study was to analyze the relationship between sedentary lifestyle and the risk of obesity in adolescents. The research design used correlation with a cross-sectional approach. The population in this study were all adolescents in the Tuban D3 Nursing Study Program, Academic Year 2023/2024, totaling 221 people, a sample size of 142 people, simple random sampling technique. The research instrument used a knowledge questionnaire and the Adolescent Sedentary Activity Questionnaire (ASAQ). Data analysis used the chi square test. The results showed that almost all adolescents had a high sedentary lifestyle, namely 116 adolescents (81.7%), but were not at risk of obesity, namely 112 adolescents (78.9%). The results of statistical tests using chi square obtained a value of r = 0.788 greater than that set at <0.05. These results indicate that there is no relationship between sedentary lifestyle and the risk of obesity in adolescents. Obesity is caused by many factors that influence each other. By understanding the causes of obesity, prevention efforts can be made through the implementation of a healthy lifestyle.